Denitrifying biofilm processes for wastewater treatment: developments and perspectives. Issue 1 (30th October 2020) - Wu, Lan; Wei, Wei; Xu, Juan; Chen, Xueming; Liu, Yiwen; Peng, Lai; Wang, Dongbo; Ni, Bing-Jie
Abstract : Biofilms can retain microorganisms with very different growth kinetics and different electron acceptor preferences, due to their natural redox zonation. Abstract : Biofilms can retain microorganisms with very different growth kinetics and different electron acceptor preferences, due to their natural redox zonation. Denitrifying biofilm processes are crucial biological processes for the treatment of nitrogen-polluted water. Heterotrophic, autotrophic, and methane-supported denitrifying biofilms have been widely utilized for removing nitrogenous contaminants in recent years. Heterotrophic denitrification is a conventional approach to conduct a respiratory process with nitrate or nitrite as the terminal electron acceptor and organic carbon serving as the main electron donor. Autotrophic denitrification is a cost-effective process for nitrogen removal with reduced inorganic compounds acting as the electron donor, such as hydrogen and sulfur. Methane could also be used directly as an electron donor to drive denitrification in the methane-based denitrification process. While the controlled biofilm-based systems are capable of enhancing the nitrogen removal efficiency by these denitrifiers, this review aimed to provide a comprehensive and up-to-date summary of these important denitrifying biofilm processes in attached-growth reactors from the perspectives of microbiology, reactor configurations, controlling factors, nitrous oxide emissions, and coexistence with other microorganisms. The technical challenges and associated strategies towards improving the performance of each denitrifying biofilm process are then discussed. The outlook for the larger engineering scalability of these processes is also put forward to facilitate their applications for higher treatment capacities.